Reconstruction of National Road Regulations in Regency/City Areas to Achieve Public Welfare Based on Progressive Law - Miyadi, ‎ (KnE Social Sciences, 2025)
This paper aims to analyze and reconstruct the regulation of national roads located within regency/city administrative areas in Indonesia. Despite their national status, these roads are often neglected in terms of maintenance and responsiveness to local needs due to administrative fragmentation. This study employs a normative-juridical approach enriched by progressive legal theory. Through doctrinal analysis and legal comparison, it finds that current regulations, particularly Law No. 38 of 2004 on roads, lack synchronization with decentralization principles as outlined in regional autonomy laws. The paper proposes a progressive legal reconstruction, recommending an integrated regulatory model involving local governments in national road management based on the principles of subsidiarity, co-administration (medebewind), and local responsiveness. This model is expected to increase the functionality of national roads, support economic mobility, and ultimately promote public welfare.